Halloween kills : the official movie novelization - Waggoner, Tim (Titan Books, 2021)
"Minutes after Laurie Strode, her daughter Karen, and granddaughter Allyson left masked monster Michael Myers caged and burning in Laurie's basement, Laurie is rushed to the hospital with life-threatening injuries, believing she finally killed her lifelong tormentor. But when Michael manages to free himself from Laurie's trap, his ritual bloodbath resumes. As Laurie fights her pain and prepares to defend herself against him, she inspires all of Haddonfield to rise up against their unstoppable monster. But as a group of other survivors of Michael's first rampage decide to take matters into their own hands, a vigilante mob forms that sets out to hunt Michael down. Evil dies tonight."--Amazon.